Simulation of comprehensive practical lessons on firefire and physical training of police employees - Polyansky P.G.; Troyan E.I. (Theory and Practice of Physical Culture, 2023)
The results of the study revealed the effectiveness of modeling complex practical exercises aimed at training police officers in the complex use of physical force and firearms.